Pengaruh Sustainability Report Terhadap Kinerja Perusahaan Non Keuangan - Sunatun Sunatun; Annisa Hafifah Latifah; Rizka Kurniawati; Erlina Sari Pohan (Prosiding Amal Insani Foundation, 2023)
The purpose of this study is to determine the effect of the disclosure of the sustainability report on the economic dimension of the company’s performance as proxied by Return On Asset (ROA), to determine the effect of the disclosure of the environmental dimension of the sustainability report to the company’s performance(ROA), to determine the effect of the disclosure of the social dimension of the sustainability report to the company’s performance(ROA), to determine the effect of the disclosure of the sustainability report to the dimensions of the economy, the environment, and the social simultaneously on the company’s performance(ROA) in non-financial companies listed on the Indonesian Stock Exchange in 2015-2019. The method used in this research is a quantitative method, while the type of data is secondary data. The population in this study were non-financial companies listed on the Indonesian Stock Exchange in 2015-2019, the sample used is 11 companies out of 575 companies. Data was processed using SPSS v.23. The result of the study show that partially the disclosure of the sustainability report of the economic dimension has a significant postive effect on the company’s performance, partially the disclosure of the environmental dimension of the sustainability report has no significant effect on the company’s performance, partially the disclosure of the sustainability report of the social dimension has a significant negative effect on the company’s performance. Simultaneously, the disclosure of the sustainability report of the economic, environmental, and social dimensions has a significant positive effect on the company’s performance.